1992
DOI: 10.3109/03009749209095074
|View full text |Cite
|
Sign up to set email alerts
|

A Doubleblind Comparison of the Gastroduodenal Safety and Efficacy of Diclofenac and a Fixed Dose Combination of Diclofenac and Misoprostol in the Treatment of Rheumatoid Arthritis

Abstract: This double-blind, parallel group study was conducted to evaluate the gastroduodenal safety and antiarthritic efficacy of a fixed combination of diclofenac sodium 50 mg and misoprostol 200 mcg, compared with a combination of diclofenac 50 mg and placebo. Three hundred and thirty-nine patients with rheumatoid arthritis and no significant gastric or duodenal mucosal damage were enrolled and received study medication (diclofenac/misoprostol, 164; diclofenac/placebo, 175) BID or TID for 12 weeks. Posttreatment gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…Misoprostol is a synthetic prostaglandin [15]that is effective in the treatment and prevention of gastrointestinal complications in long-term NSAID users when compared with placebo [16, 17, 18, 19]and sucralfate [20]. However, despite the efficacy of misoprostol, poor patient compliance is evident with this drug because of the need to ingest up to four tablets per day and because of the high incidence of dose- and drug-related adverse events such as diarrhea, abdominal pain, and flatulence [17, 21].…”
Section: Introductionmentioning
confidence: 99%
“…Misoprostol is a synthetic prostaglandin [15]that is effective in the treatment and prevention of gastrointestinal complications in long-term NSAID users when compared with placebo [16, 17, 18, 19]and sucralfate [20]. However, despite the efficacy of misoprostol, poor patient compliance is evident with this drug because of the need to ingest up to four tablets per day and because of the high incidence of dose- and drug-related adverse events such as diarrhea, abdominal pain, and flatulence [17, 21].…”
Section: Introductionmentioning
confidence: 99%
“…[22) All economic evaluations use the probability of developing an endoscopically detected gastric ulcer with misoprostol prophylaxis observed in a 3-month double-blind randomised trial by Graham et al 17 ] Although the association between dyspepsi~ and mucosal lesions is weak, [21] the ulcer rate of 21.7% observed by these investigators is likely to be high. In clinical studies conducted by Verdickt et al [8] and Melo Gomes et al, [9] the absolute risk of endoscopically confirmed gastroduodenal ulcer without misoprostol prophylaxis was 2% for diclofenac, [8] 8.6% for naproxen and 10.3% for piroxicam; [9] these rates are considerably lower than those used in the economic evaluations. Using the smaller absolute risk reduction in the economic evaluations would have resulted in net costs for misoprostol in all studies.…”
Section: Assumptions About the Reduction In Gi Eventsmentioning
confidence: 94%
“…18 The rate of 21.7% observed in the study of Graham et al 15 and used by four studies 9 " 12 is likely to be high. In recent studies by Verdickt et al 19 and Graham et al 20 on cotherapy of misoprostol with different NSAIDs, the absolute endoscopic gastric ulcer risk was 4% 19 and 9% 20 in the placebo group, which is considerably smaller than the one used in the economic evaluations. Using the correspondingly smaller absolute risk reduction would have led to net costs for misoprostol in all studies.…”
Section: Critique Of the Studiesmentioning
confidence: 95%